Strategic Use of Karma in Lan Cao’s Monkey Bridge - Huang, Zhi (Religions, 2024)
Most critics focus on the pain and suffering of the first-generation Vietnamese immigrants depicted in Lan Cao’s Monkey Bridge. This paper explores how Cao strategically uses the philosophy of karma in Vietnamese Buddhism to provide a method for alleviating their suffering in this novel. It argues that she employs karma to investigate the origins of the adversity and trauma experienced by the first-generation Vietnamese immigrants, including the pro-American attitude of the early Vietnamese authorities during the Vietnam War, the imperialistic actions of the United States, and the resulting karmic consequences. In addition, they demonstrate, through actions like forming “hui”, a way to change their fate and heal their trauma for later generations of Vietnamese immigrants, emphasizing positive transformation of karma. This paper suggests that the Buddhist philosophy of karma provides an effective strategy for Vietnamese American immigrants to reflect on the Vietnam War, overcome adversity, and heal their own trauma.